Design, development and characterization of a novel and innovative exhaust filter media for the global automotive industry. Issue 18 (November 2016) - Howarth, J; Anand, SC
This paper discusses that three-dimensional (3D) warp knitted spacer structures offer significant attributes that create sustainable production advantages in dry exhaust systems for the automotive paint industry. The advantages that are offered include improved airflow and the potential to combine to a composite solution with a high paint holding capacity; this concept of filtration also offers the possibility of a durable filter capable of industrial cleaning and reuse numerous times. The paper describes the innovation of these 3D warp knitted spacer filters from theoretical and traditional filtration aspects, followed by an empirical characterization that justifies commercial trials within the industry.